Berhikmat dalam Mengelola Amarah: Studi Topikal Penggunaan Kata Marah dalam Kitab Amsal - Mokar, Timothy Wesley; Kristiawan, Ragil (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2024)
One of the important pieces of advice from the book of Proverbs is about how to manage anger. Uncontrolled anger often brings bad things to a person. The word anger itself appears 19 times in this book. Two main questions are asked in this study: how does Proverbs view anger? How to manage anger wisely in humans according to Proverbs? By using a topical approach in the Book of Proverbs, two main things are concluded. First, anger is the root of stupidity and the enemy of wisdom. Anger will always have a bad impact and destroy peace among fellow human beings. Second, Proverbs also provides wise advice in managing anger. A calm and careful attitude is needed when someone is dealing with anger. Managing anger is basically the same as managing good emotions. A patient and wise attitude can extinguish the anger of others. As a practical application, God's people today must really be able to manage anger because uncontrolled anger will only bring harm.